Influence of geosynthetic and rubber inclusions on shear and breakage behavior of rail track ballast. - Venuja, S.; Navaratnarajah, S.K. (International society for Soil Mechanics & Geotechnical Engineering, 2020)
Ballasted rail tracks and concrete slab tracks are the two major types of rail track structures all around the world. Due to the ease of construction and relatively low initial cost, ballasted tracks are popular compared to slab tracks. Ballast is a coarse and highly angular material with high shear strength and bearing capacity. Ballast is getting degraded over time due to the continuous transmission of energy by the wheel loads from freight and passenger trains, which leads to track settlement, track degradation, and high cost for mainte- nance. Rubber mats and geogrids are used in railways to improve the performance of ballast used in rail tracks. In this study, several tests were conducted on fresh ballast and ballast stabilized with geosynthetic and rubber under direct shear loadings to check the performance of ballast. The outcomes in this study show that the com- bination of rubber mats with geogrid works well in terms of reducing ballast degradation and maintaining shear resistance of the ballast layer.